Synthesis of some natural sulphonamide derivatives as carbonic anhydrase inhibitors - GOKCEN, Taner; AL, Melike; Topal, Meryem; GÜLÇİN, İlhami; OZTURK, Turan; Goren, AHMET CEYHAN; GÖREN, AHMET CEYHAN (My University, 2017)
Carbonic anhydrase inhibitor; sulphonamides; p-hydroxybenzoic acid; 3,4,5-trihydroxybenzoic acid (gallic acid).Carbonic anhydrase inhibitors are both in clinical use as antiglaucoma, diuretics, antiepileptics and management of altitude sickness, and under investigation as anticancer, anticonvulsant and antiobesity agents. Sulphonamides have been known for decades as carbonic anhydrase inhibitors and are in clinical use. Sulphonamide derivatives of p-hydroxybenzoic acid and 3,4,5-trihydroxybenzoic acid (gallic acid) were synthesized and their inhibition values over hCA I and hCA II isozymes, purified from human erythrocyte cells by Sepharose-4B-L-tyrosine-sulphanilamide, were determined. Compounds synthesized showed efficient carbonic anhydrase inhibition activity at low nM levels.